Managing Diversity: The Government Of A Malaysian Hawker Place (Malaysian Management Journal, 2015)
Selling and consuming street food has a long tradition in urban areas of Asia. While the preparation of food, the appropriation of space, and the sale itself follow certain rules, some of them are informal and not always in line with government regulations. However, even though the street vendors (or hawkers) are practicing their trade in a gray area between formality and informality many hawker places function surprisingly well. It is the aim of the paper to analyze the functioning of such a hawker place. As case study serves Changlun, a small town in the Malaysian state of Kedah, where qualitative interviews with hawkers but also officials were conducted. Results indicate that the government of this hawker place is a consequence of an intricate entanglement of practices, which include a tolerant administration but also compliant hawkers and customers liking this place. However, this entanglement is not without conflicts and problems. The hawkers are economically vulnerable and do not have many alternatives to generate income. Consequently the paper ends with recommendations that should enable the functioning of a hawker place as a traditional and well-regarded place to meet and eat and a space for underprivileged people to earn an income.